Diagnostic Approaches for Clostridioides difficile Infection - Berry, Parul; Khanna, Sahil (Infectious disease clinics of North America, 2025)
This article offers a clinically focused overview of Clostridioides difficile infection (CDI) diagnosis, emphasizing the need to test only symptomatic patients and to distinguish true infection from colonization. It reviews multistep diagnostic algorithms that pair glutamate dehydrogenase (GDH) testing or nucleic acid amplification tests (NAAT) with toxin assays to improve accuracy. The limitations of PCR-only approaches are discussed, with a strong emphasis on clinical correlation. Guideline-based recommendations are integrated throughout, providing evidence-based direction for clinicians managing CDI in both inpatient and outpatient settings.